New Thoughts on the Black Arts Movement - Collins, Lisa Gail (Book collections on Project MUSE., 2006)
During the 1960s and 1970s, a cadre of poets, playwrights, visual artists, musicians, and other visionaries came together to create a renaissance in African American literature and art. This charged chapter in the history of African American culture-which came to be known as the Black Arts Movement-has remained largely neglected by subsequent generations of critics. New Thoughts on the Black Arts Movement includes essays that reexamine well-known figures such as Amiri Baraka, Larry Neal, Gwendolyn Brooks, Sonia Sanchez, Betye Saar, Jeff Donaldson, and Haki Madhubuti. In addition.